Exploring the Factors Accelerating the Electric Motorcycle Adoptions: Insights from Theory of Planned Behavior and Travel Behavior - Muhammad Hafiz Aditya; Yuniaristanto Yuniaristanto; Wahyudi Sutopo (Universitas Muhammadiyah Magelang, 2024)
Indonesia is a densely populated country where most people use motorcycles for mobility. With increasing carbon emissions, Indonesia plans to migrate conventional motorcycles toward electric ones by 2040. However, the adoption process of electric motorcycles is relatively slow, considering that the number of electric motorcycles is still far from the government's target. This study aims to investigate what factors influence the adoption process of electric motorcycles in Indonesia. Based on 906 samples, an analysis was conducted using a hybrid choice model on willingness to pay more, which considered three components: socio-demographics, Theory of Planned Behavior (TPB), and travel behavior patterns. The results showed that all three components significantly affect the willingness to pay more. Individuals who are older, highly educated, high-income, use public or environmentally friendly transportation, and have a low frequency of mobility for work purposes are more likely to purchase an electric motorcycle. The results of this study provide a new perspective in the unique context of electric motorcycle adoption in Indonesia and conditions that still need improvement when related to the government's long-term targets. This research will be helpful for governments and manufacturers by providing the characteristics of people who are more likely to purchase an electric motorcycle.